Utilization of Waste Plastic Materials in Road Construction - Raut, Aditya; Dhengare, Sagar W.; Dandge, Ajay L.; Nikhade, Harshal R. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2016)
Plastics are user friendly but not eco-friendly as they are non biodegradable. Generally it is disposed by way of land filling or incineration of materials which is extremely risky. This waste plastic can be partially mixed with material use for road construction. In conventional road making process bitumen is used as binder. Such bitumen can be modified with waste plastic pieces. This waste plastic modified bitumen mix shows better binding property, stability, density and more resistant to water. Worldwide use of waste material in road construction is being increasingly encouraged so as to reduce environmental impact. The use of this innovative technology will strengthen the road construction and increase the road life as well as will help to utilization of waste plastic material. Plastic roads would be a blessing for hot and extremely humid climate, where temperatures normally cross 50°C and abundant rains create damage, leaving most of the roads with big potholes. The main aim of this study is to focus on using the available waste/recycled plastic materials and waste rubber tires present in abundant that can be used economically and conveniently. Using this technique for road construction proves ecofriendly, economical and use of plastic will also give strength in the sub-base course of the pavement.